TOOTHPASTE. - Sotimova Shohida Mansur daughter. (TADQIQOTLAR, 2025)
Abstract: Toothpastes are daily oral care products, the chemical composition of which is constantly changing due to production competition. It makes even more difficult for dentists to decide which toothpaste is best to recommend and for patients to choose one. The purpose of the article is to investigate the effect of different types of toothpaste and their ingredients. Recommendations for toothpaste choice and usage were developed from the best evedince available.